2019
DOI: 10.1177/1524839919837619
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy and Public Policy Perceptions and Involvement of College Health Promotion Students

Abstract: Understanding the advocacy and public policy training needs of our future health promotion workforce is crucial if we are to prepare them to meet their professional responsibilities. The purpose of this study was to examine health promotion students’ advocacy/public policy involvement, training, and perceptions. Electronic surveys were disseminated nationwide to college students in health education and closely related programs. Of 477 student respondents, the most frequently indicated advocacy/public policy ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Soft skills mastery is not unilaterally delegated to the University, because the presences of students in previous classes are not considered. There needs to be an increase in training at the previous educational levels in accordance with knowledge, self-efficacy, and advocacy/public policy involvement (Conrad, Becker, Brandley, Saksvig, & Nickelson, 2019). In addition, they are prepared as intellectuals with critical, democratic and constructive thinking able to make specific changes for the nation and state.…”
Section: Discussionmentioning
confidence: 99%
“…Soft skills mastery is not unilaterally delegated to the University, because the presences of students in previous classes are not considered. There needs to be an increase in training at the previous educational levels in accordance with knowledge, self-efficacy, and advocacy/public policy involvement (Conrad, Becker, Brandley, Saksvig, & Nickelson, 2019). In addition, they are prepared as intellectuals with critical, democratic and constructive thinking able to make specific changes for the nation and state.…”
Section: Discussionmentioning
confidence: 99%
“…The policy-related skills gained in these courses, such as identifying policy audiences, reading and understanding the policy language, collaborating with advocacy organizations, displaying policy-relevant data, and crafting policy-oriented materials, are rare among undergraduates. According to a national survey, only 6% of students have “provided written reports, consultation, research, or other such assistance to a public official in support of or opposition to a public policy issue” (E. J. Conrad et al, 2019, p. 735), and only 9% have “participated in an advocacy committee or coalition that takes action to influence public policy issues” (E.…”
Section: Discussionmentioning
confidence: 99%
“…J. Conrad et al, 2019). The authors of the survey concluded that relevant training predicts advocacy and policy involvement and there is a need “to provide coursework or experiences in health promotion curriculum starting at the undergraduate level” (E. J. Conrad et al, 2019, p. 738).…”
mentioning
confidence: 99%
See 2 more Smart Citations